2013
DOI: 10.4161/cib.23125
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis ofPlasmodiumspecies specific UvrD helicase

Abstract: Malaria is still a devastating disease caused by the mosquito-transmitted parasite Plasmodium, particularly Plasmodium falciparum. During the last few years the situation has worsened in many ways, mainly due to malarial parasites becoming increasingly resistant to several anti-malarial drugs. Thus there is an urgent need to find alternate ways to control malaria and therefore it is necessary to identify new drug targets and new classes of anti-malarial drugs. A malaria vaccine would be the ultimate weapon to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The in silico analysis of amino acid sequence of PfUvrD helicase revealed that it contains characteristic UvrD motifs ( Figure 6B ). Previously we have reported that all the Plasmodium species contain UvrD and P. falciparum contains the largest UvrD and this enzyme is significantly variable at the sequence and structural level among all the species of Plasmodium ( Tuteja, 2013 ). In previous studies we have reported that PfUvrD contains DNA helicase and ssDNA-dependent ATPase activities ( Ahmad et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…The in silico analysis of amino acid sequence of PfUvrD helicase revealed that it contains characteristic UvrD motifs ( Figure 6B ). Previously we have reported that all the Plasmodium species contain UvrD and P. falciparum contains the largest UvrD and this enzyme is significantly variable at the sequence and structural level among all the species of Plasmodium ( Tuteja, 2013 ). In previous studies we have reported that PfUvrD contains DNA helicase and ssDNA-dependent ATPase activities ( Ahmad et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…UvrD is a member of superfamily one and is essential for the NER and mismatch repair (MMR) to repair mismatches occurring as a result of DNA damage or during DNA replication . Remarkably, P. falciparum and other Plasmodium species contain UvrD helicase but its homolog is absent in the human host . PfUvrD is a 1441 amino acid protein of ~ 170 kDa, and its various fragments have been biochemically characterized.…”
Section: Parasite‐specific Helicase Uvrdmentioning
confidence: 99%
“…Although many putative therapeutic targets for malaria have been reported in the recent past [ 10 - 19 ] but further studies are required in order to get the insight for the successful development of suitable drugs. Helicases have also been proposed as suitable drug targets for human cancers as well as many pathogens including viruses and P. falciparum [ 20 - 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, UvrD is required for the mismatch repair (MMR) and nucleotide excision repair (NER) to repair mismatches occurring during replication or DNA lesions such as UV-induced pyrimidine dimers or more bulky adducts [ 35 , 39 , 40 ]. In a recent study we have reported the detailed biochemical characterization of the UvrD helicase from P. falciparum and have shown that it exhibits the ssDNA-dependent ATPase activity and the DNA helicase activity in 3’ to 5’ direction [ 32 , 33 , 35 ]. Recent study on UvrD in different Plasmodium species revealed that the other species of Plasmodium also contain putative UvrD helicase [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation